2016
DOI: 10.1021/acsami.6b05646
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Epithelial-to-Mesenchymal Transition Using Biomimetic Fibrous Scaffolds

Abstract: Epithelial-to-mesenchymal transition (EMT) is a well-studied biological process that takes place during embryogenesis, carcinogenesis and tissue fibrosis. During EMT, the polarized epithelial cells with a cuboidal architecture adopt an elongated fibroblast-like morphology. This process is accompanied by the expression of many EMT-specific molecular markers. While the molecular mechanism leading to EMT has been well established, the effects of matrix topography and microstructure have not been clearly elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 76 publications
1
31
0
Order By: Relevance
“…Saha et al [7] investigated the role of ECM fiber alignment on breast cancer EMT and further metastatic invasion using PCL fibers and showed that breast cancer cells increased their TGF-Beta 1 levels on aligned fibers as opposed to flat topographies. Similarly, Ravikrishnan et al [15] created an RGD functionalized fiber topography and investigated the role of fiber diameter on kidney epithelial cell (MDCK) EMT. They showed that the large diameter fibers foster MDCK cell EMT whereas small diameters promote epithelial cell cluster formation and preservation of epithelial morphology of MDCK cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Saha et al [7] investigated the role of ECM fiber alignment on breast cancer EMT and further metastatic invasion using PCL fibers and showed that breast cancer cells increased their TGF-Beta 1 levels on aligned fibers as opposed to flat topographies. Similarly, Ravikrishnan et al [15] created an RGD functionalized fiber topography and investigated the role of fiber diameter on kidney epithelial cell (MDCK) EMT. They showed that the large diameter fibers foster MDCK cell EMT whereas small diameters promote epithelial cell cluster formation and preservation of epithelial morphology of MDCK cells.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Briefly, PCL polymer solution was prepared and loaded into a syringe pump. For 5 µm diameter fibers 15% PCL dissolved in chloroform, and for 0.5 µm fibers 12% PCL dissolved in 7:3 DCM:DMF were used.…”
Section: Fabrication Of Fibrous Scaffolds and Flat Polymer Topographymentioning
confidence: 99%
See 2 more Smart Citations
“…207 Fiber-like scaffolds, designed to mimic fibrillar ECM proteins, have been shown to regulate cell migration, proliferation, and epithelial-to-mesenchymal transition (Figure 8A). 208, 209 Multiple processing strategies have been applied to develop microstructured materials, including photopatterning 210 and selective degradation, 211 as mentioned above. Such approaches yield materials that exhibit improved cell attachment and migration, 212 as well as enhanced tissue infiltration into scaffolds.…”
Section: Control Over Biocomplexitymentioning
confidence: 99%